Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3851/imp3192
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Dolutegravir/Abacavir/Lamivudine versus Current ART in Virally Suppressed Patients (STRIIVING): A 48-Week, Randomized, Non-Inferiority, Open-Label, Phase IIIb Study

Abstract: The publisher would like to report an error that appeared in a recently published article [1]. The y-axis label in Figure 3A has been corrected as of 13 September 2017 and should read 'Median increase in CD4 + T-cell counts, cells/mm 3 '. The accompanying footnote has also been amended and the correct version is shown. The authors apologize for this error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…Serious AEs and treatment discontinuations were low in both groups of an open label randomized study of participants switched to DTG/3TC/ABC from various baseline regimens at study entry (early-switch group) or at week 24 (late-switch group). 23 The most common AEs in the early-switch group were nausea (10%), fatigue (7%), diarrhea (6%), and headache (5%), which occurred in 1% of the late-switch participants during weeks 1 to 24. Psychiatric AEs were more common in the early-switch group compared to the late-switch group during weeks 1 to 24 and weeks 24 to 48 (13% versus 3% and 9%, respectively) and included mainly grade 1 and grade 2 effects.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Serious AEs and treatment discontinuations were low in both groups of an open label randomized study of participants switched to DTG/3TC/ABC from various baseline regimens at study entry (early-switch group) or at week 24 (late-switch group). 23 The most common AEs in the early-switch group were nausea (10%), fatigue (7%), diarrhea (6%), and headache (5%), which occurred in 1% of the late-switch participants during weeks 1 to 24. Psychiatric AEs were more common in the early-switch group compared to the late-switch group during weeks 1 to 24 and weeks 24 to 48 (13% versus 3% and 9%, respectively) and included mainly grade 1 and grade 2 effects.…”
Section: Resultsmentioning
confidence: 96%
“…Virologic suppression was evaluated in 4 studies that switched patients to a DTG-based regimen from baseline ART (Table 2). 2325,31 Each study showed high level of virologic suppression after the switch, ranging from 92% to 97%.…”
Section: Resultsmentioning
confidence: 99%
“…In our study we observed no impact of previous NRTIs resistance according to the historical GRT on the risk of VF of ART composed by DTG+2 NRTIs. This finding is interesting because no information is available from randomized clinical trial due to the exclusion of patients with previous NRTIs mutations [6,7]. Nevertheless, a recent large observational study conducted in several European countries confirmed the absence of the impact of M184V/I on the virological efficacy of ABC/3TC/DTG regimen in switch strategy [15].…”
Section: Immune-virological Status and Years On Art No Significant Amentioning
confidence: 94%
“…In the past decades antiretroviral therapy (ART) has dramatically changed the natural history of HIV-1 infection by transforming an invariably fatal disease into a chronic one [1]. The advent of a new class of antiretroviral, integrase inhibitors (INIs), has provided new effective and well tolerated ART options both in naïve [2][3][4][5] and experienced patients [6][7]. Simplification strategies based on INIs are increasingly used in clinical practice with the aim to improve the tolerability and to avoid potential long-term metabolic untoward effects of other antiretrovirals, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation